Implementasi E-Court Terhadap Pelayanan Administrasi Perkara Di Pengadilan Agama Gresik - Miftakur Rohman; Ayu Kartika (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2022)
In the current development of digital technology, the Court has experienced a few obstacles since the emergence of the 2019 covid pandemic virus outbreak, including the Gresik religious court which requires restrictions on public crowds. With these obstacles, the court issued a case registration system using E-court where the application is contained in Supreme Court Regulation No. 3 of 2018 concerning the case registration process which is carried out electronically. How is the implementation of E-court on administrative services at the Gresik Religious Court and what are the factors that support and hinder the implementation of E-court on administrative services at the Gresik Religious Court. Based on monitoring and research, the implementation of E-court on administrative services at the Gresik Religious Court has been carried out well in accordance with Supreme Court Regulation No. 3 of 2018 which is based on the principles of fast, easy, simple and low cost. Factors that support the implementation of the E-court are the existence of sufficient technical facilities such as computers and internet networks, but sometimes there is interference with the signal which makes the upload of data transmission long and this is part of the obstacle. The convenience of this technology is in great demand by advocates because it makes it easy, but it is considered difficult for some people due to the lack of human resources and government socialization.